Impact assessment of a solar powered water treatment project - Mwakangale, Jacqueline C.D (2015)
Water treatment technologies are seen as the best alternative to be considered for adoption in developing countries where access to portable water supply that is free of pathogens is yet a challenge. This study intended to assess impact brought forth by a project, which employed a water treatment technology in rural settings of Morogoro Region in Tanzania. The project used solar photovoltaic panels to trap solar energy, converted to mechanical power to treat water with the help of sterilization ultraviolet membrane.